The Influence Of Subject Norms And Word Of Mouth (Wom), On Vısıtıng Decısıons (Case Study in Madiun City Waterfront Park) - Rizal Ula Ananta Fauzi; Sindi Robianti (Cita Konsultindo Research Center, 2024)
This research aims to determine the influence of subjective norms and word of mouth (WOM) on visiting decisions among visitors to the Bantaran Park tourist attraction, Madiun City. The type of research used in this research is a quantitative approach. The research uses multiple linear regression techniques. Sampling used the Probability Sampling technique. The sample used was 261 respondents. Based on statistical test results, it shows that partially subjective norms do not have a positive and significant effect on the decision to visit, word of mouth (WOM) has a positive and significant effect on the decision to visit, decision to visit the Taman Bantaran Madiun City tourist attraction.